Evaluation of The Antibacterial Activity of Some Extracts of Date Palm (Phoenix Dactylifera) and Date Pits of The Bakrari Variety - Faed, Kholoud Alhadi; Ali, Hasan Mohamed (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Date fruits have been used for nutritional and therapeutic purposes in various parts of the world, especially in the Middle East. It is rich in many essential nutrients and a wide range of antioxidant compounds. Antibiotics play a fundamental role in treating infections. However, some pathogenic bacteria have begun to develop resistance to them, causing chronic infections. This study aimed to evaluate the antibacterial activity of five extracts of Bakrari dates and one extract specific to date pits, namely ethyl acetate extract: ethanol (1:1), chloroform: ethanol (1:1), ethanol and acetone: water (1:1), ethanol: water (1:1), and propanol extract specific to date pits to determine their antibacterial activity against four types of pathogenic bacteria, namely Escherichia coli, Klebsiella pneumoniae, Staphylococcus aureus, and Acinetobacter. spp. The results obtained showed that the ethyl acetate extract had a significant antibacterial activity compared to other extracts, as it showed the highest inhibition zone against S. aureus bacteria with an average inhibition zone (40 mm), and other extracts showed a diverse effect against other types of used bacteria, such that the effectiveness of the extract increases with increasing concentration. It is concluded that the Bakrari date fruits and date pits contain biologically active substances that have the ability to inhibit bacteria.
Keywords: Bakrari date; Alcoholic extract; Pathogenic bacteria; Antibiotic; Antibacterial activity